Homer : the Odyssey - Griffin, Jasper (Landmarks of world literature., 2004)
This handy guide will introduce students to a text that has been fundamental to literature for nearly 3000 years. It gives readers a summary of The Odyssey and examines its structure. The values and techniques of the poem are clearly outlined, as are the reasons for its longstanding appeal.